Thermoplastic Elastomers Synthesis and Applications - Kumar Das, Chapal (IntechOpen, 2015)
Thermoplastic elastomers (TPEs), commonly known as thermoplastic rubbers, are a category of copolymers having thermoplastic and elastomeric characteristics. A TPE is a rubbery material with properties very close to those of conventional vulcanized rubber at normal conditions. It can be processed in a molten state even at elevated temperatures. TPEs show advantages typical of both rubbery materials and plastic materials. TPEs are a class of polymers bridging between the service properties of elastomers and the processing properties of thermoplastics. Nowadays, the best use of thermoplastics is in the field of biomedical applications, starting from artificial skin to many of the artificial human body parts. Apart from these, thermoplastic elastomers are being used for drug encapsulation purposes, and since they are biocompatible in many cases, their scope of applications has been broadened in the biotechnological field as well. The present book highlights many biological and biomedical applications of TPEs from which the broader area readers will benefit.